Investment Behavior: Factors that Limit African Americans' Investment Behavior - Crystal Hudson; John Young; Sophia Anong; Elania Hudson; Edward Davis (Journal of Financial Therapy, 2018)
This study investigated factors that are likely to limit African Americans’ investment activity in the stock market by triangulating data from the 2015 FINRA Financial Capacity Study and a Financial Behavior/Capacity survey that targeted African Americans. The financial survey revealed the top self-reported reasons these African Americans gave for not investing which were, “I don't understand how the stock market works”, “I don't make enough money” and “I don’t want to lose my money". Logistic regression results for the FINRA African American sample indicate that those with more financial knowledge, those who participated in financial education, and those who were financially socialized by parents were more likely to invest. In terms of magnitude, financial education had a larger impact on the FINRA African Americans than on the FINRA Caucasians and parental financial socialization and financial knowledge had larger impacts on the FINRA Caucasians.
Keywords: African Americans; Investing; Financial Knowledge; Financial Socialization; Financial Education